2017
DOI: 10.1161/strokeaha.116.014738
|View full text |Cite
|
Sign up to set email alerts
|

Valproate Reduces Delayed Brain Injury in a Rat Model of Subarachnoid Hemorrhage

Abstract: Delayed cerebral ischemia (DCI) is a common and feared complication after subarachnoid hemorrhage (SAH), which occurs in approximately one third of patients. 1 The mechanisms that are involved in DCI development are largely unknown. Spreading depolarizations (SDs) have been suggested to be associated with DCI in experimental and clinical SAH studies. 2 SDs are waves of depolarizations of neurons and glial cells that spread across brain tissue at a speed of 2 to 6 mm/min. 3 SD is the underlying mechanism of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The blood leaking into the subarachnoid space following SAH has the potential to cause severe brain edema and subsequent neurological deficits [35,36]. In addition, the toxic agents resulting from the breakdown of the blood cells cause further neural death, leading to permanent neurological deficits, including cognition, memory and learning disabilities [37]. In this study, we found that BMS-470539 treatment significantly alleviated neurological deficits and reduced brain edema at 24 h after SAH.…”
Section: Discussionmentioning
confidence: 55%
“…The blood leaking into the subarachnoid space following SAH has the potential to cause severe brain edema and subsequent neurological deficits [35,36]. In addition, the toxic agents resulting from the breakdown of the blood cells cause further neural death, leading to permanent neurological deficits, including cognition, memory and learning disabilities [37]. In this study, we found that BMS-470539 treatment significantly alleviated neurological deficits and reduced brain edema at 24 h after SAH.…”
Section: Discussionmentioning
confidence: 55%
“…200 mg/kg VPA is known to exert neuroprotective effects by reducing hippocampal neuron loss and improving cognitive function after cerebral ischemia in rats [ 33 ]. A previous study showed that the treatment of VPA (300 mg/kg) significantly reduced the growth of brain lesions with respect to delayed cerebral ischemia after subarachnoid hemorrhage [ 34 ]. Hemorrhage volume is a key factor related to most accepted predictors of ICH prognosis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the present study has some limitations. VPA may exert a variety of protective effects through various signaling pathways in the central nervous system [ 34 , 36 ]. In the present study, we only pay attention to the effect of VPA on BBB.…”
Section: Discussionmentioning
confidence: 99%
“…The imaging was performed accordingly to previously described protocols . Although pre‐clinical rodent brain MRI at 9.4T can be acquired with 1‐mm slice thickness for high‐resolution morphological analysis, it was deemed appropriate to choose a slice thickness of 2 mm in this study considering that this is a common choice of spatial resolution for perfusion MRI investigations …”
Section: Methodsmentioning
confidence: 99%